Therapeutic pedagogy, the individualization of education as a response to diversity (Journal of Parents and Teachers, 2023)
Within the programs related to inclusive education that a center can carry out with the aim of responding to the diversity of its students, the therapeutic pedagogy program becomes a benchmark in this regard, since through individualization of teaching tries to give a personalized response to students with special educational needs so that they can fully develop their full potential.
Keywords: diversity; inclusive education; therapeutic pedagogy; special educational needs; individualization of teaching